2014 Joint IEEE International Symposium on the Applications of Ferroelectric, International Workshop on Acoustic Transduction M 2014
DOI: 10.1109/isaf.2014.6922970
|View full text |Cite
|
Sign up to set email alerts
|

Development of ferroelectric RAM (FRAM) for mass production

Abstract: we have developed ferroelectric capacitor fabrication technique and a new sensing amplifier circuit to realize lowvoltage and high-density FRAM. Improvement of IrO x top electrode near the ferroelectric interface successively lowers operation voltage. And our developed "Dual Reference Sensing Amplifier" enables to commercialize highly-reliable FRAM with memory density of 4Mb or larger. FRAM, Feroelectric, PZT, IrO, Dual SensingI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Ramtron International Corporation presented the first commercial FRAM in 1988 [8]. FRAM is an advanced non-volatile memory that marketed earlier than its counterparts like MRAM, PCRAM, ReRAM [9].…”
Section: Fram/feram (Ferroelectric Ram)mentioning
confidence: 99%
“…Ramtron International Corporation presented the first commercial FRAM in 1988 [8]. FRAM is an advanced non-volatile memory that marketed earlier than its counterparts like MRAM, PCRAM, ReRAM [9].…”
Section: Fram/feram (Ferroelectric Ram)mentioning
confidence: 99%
“…FeRAM NVM based on lead zirconium titanate (PZT) -ferroelectric capacitor materials exhibit superior performance in flexible NVM in terms of low operation voltage (1.5 V), low cost per bit, and high switching speeds (~70 ns for the actual array) [24]- [26]. Ghoneim et al demonstrated the highest ever level of endurance (10 9 fatigue cycles for unbent and 10 10 for bent) before losing ~50% polarization for PZT base capacitor and stability of non-volatile charges (as a difference of switching and non-switching polarization) shown in Fig.…”
Section: B Memory Management Modulementioning
confidence: 99%
“…Rigid ferroelectric random access memories (FeRAM) have already made a great leap by their introduction to the market; hence, it is a relatively mature technology compared to other emerging NVM technologies. FeRAMs are commercially available in Texas Instruments' microprocessors and Fujitsu's RF tags [222][223][224]. The commonly used ferroelectric material in FeRAM is lead zirconium titanate (Pb1.1Zr0.48Ti0.52O3-PZT) due to its high switching speed [225,226], low cost per bit ($/bit), and low operation voltage [227,228].…”
Section: Flexible Ferammentioning
confidence: 99%